Strong electric field modulation of transport in PVDF/MWCNT nanocomposite near the percolation threshold - Chanmal, Chetan; Deo, Meenal S.; Rana, Abhimanyu; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2011)
A nanocomposite comprising of multiwalled carbon nanotubes (MWCNT) embedded in ferroelectric Poly(vinylidene fluoride) PVDF polymer matrix is examined for electric field induced transport modulation. The pulsed laser deposition (PLD) grown thin films of the nanocomposite with different MWCNT content were characterized. When used as a channel layer in a field effect transistor configuration, a strong electric field modulation of the transport was realized just below the percolation threshold. We believe that this nanocomposite non-percolating channel concept can provide several opportunities for FET devices for organic electronics. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Field effect device; pulsed laser deposition; PVDF; Scanning tunneling microscopy